Does global positioning system-based navigation dependency make your sense of direction poor? A psychological assessment and eye-tracking study - Yan, Wanling; Li, Jialing; Mi, Can; Wang, Wei; Xu, Zhengjia; Xiong, Wenjing; Tang, Longxing; Wang, Siyu; Li, Yanzhang; Wang, Shuai (Frontiers in Psychology, 2022)
Background: Global positioning system (GPS)-based navigation apps are very useful in our lives. However, whether and how the usage of these apps affects spatial cognition and the sense of direction is still unclear. Methods: A total of 108 individuals were recruited and completed the GPS dependence, internet gaming behavior, and impulsivity test using scales. The eye-tracking-based general mental rotation (MR) task and target finding (TF; require individuals to find a target specified in a 3D street map in a rotated version of top 2D view map) task were used to assess their spatial cognition and the sense of direction. The correlation was used to relate GPS navigation usage, spatial cognition ability, and impulsivity. Subgroup analyses stratifying by gaming hours of individuals (< 2 h or >= 2 h) or maps (countryside or city) in TF task were performed. The moderating and mediating effect analyses were conducted to verify these relationships. Results: The GPS dependency score was nominal positively correlated with fixations in the TF task in the entire cohort (r = 0.202, unadjusted p = 0.036); it was significant in city (r = 0.254, p = 0.008) and gaming time of < 2 h (r = 0.459, p = 0.001) subgroups. The high-score (upper 30%) group of GPS dependency had more fixations on the original target building in the training area and indicative building in the test area than the low-score (lower 30%) group. GPS dependency was not associated with the correct rate and reaction time in the TF task or any of the indicators in the MR task (p > 0.05). The GPS dependency mediated the indirect effect of impulsivity on the fixations on TF. The internet gaming time moderated the association between GPS dependency and fixations on TF. Conclusion: The dependency on GPS-based navigation apps was associated with impaired spatial cognition but may not significantly affect the sense of direction.